2009
DOI: 10.1111/j.1600-0501.2009.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone augmentation ability of autogenous bone graft particles with different sizes: a histological and micro‐computed tomography study

Abstract: SB follows a smooth osteogenic process, whereas it is not effective in volume augmentation. LB is superior to SB in augmentation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…AGs have been recommended by many authors for both periodontal defects and around dental implants . However, it was reported that AGs showed continuous bone volume reduction during healing and follow‐up periods (14).…”
Section: Discussionmentioning
confidence: 99%
“…AGs have been recommended by many authors for both periodontal defects and around dental implants . However, it was reported that AGs showed continuous bone volume reduction during healing and follow‐up periods (14).…”
Section: Discussionmentioning
confidence: 99%
“…12 They have also been used for different purposes in dental research. [13][14][15][16] It has been found that using micro-CT images is a reliable method in making linear measurements compared to direct measurements, 17 and that the ability of micro-CT…”
Section: Introductionmentioning
confidence: 99%
“…; Kon et al. ). Another invasive method to get information on the bone quality is the subjective perception of density by the surgeon during the preparation and placement of oral implants or the objective monitoring of the insertion torque (Tricio et al.…”
mentioning
confidence: 97%